1998
DOI: 10.1182/blood.v91.4.1178
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Treatment, and Outcome of Central Nervous System Recurrence in Adults With Intermediate-Grade and Immunoblastic Lymphoma

Abstract: To evaluate the incidence, risk factors, and outcome of central nervous system (CNS) recurrence in adult patients with non-Hodgkin's lymphoma, we evaluated 605 newly diagnosed patients with large-cell and immunoblastic lymphoma who participated in prospective chemotherapy studies. The Kaplan-Meier estimate of probability of CNS recurrence at 1 year after diagnosis was 4.5% (95% confidence interval [CI], 4.4 to 4.6). Twenty-four patients developed CNS recurrence after a median of 6 months from diagnosis (range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
158
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(163 citation statements)
references
References 28 publications
3
158
1
1
Order By: Relevance
“…This may again reflect the superior effect of rituximab in controlling systemic disease. The reported parenchymal recurrences in earlier studies were estimated at only 25% (van Besien et al, 1998;Hollender et al, 2002;Tilly et al, 2003). However, we observed a strikingly higher proportion of parenchymal-only relapses (62Á5%) compared to leptomeningeal or parenchymal/leptomeningeal relapses as seen by some groups (Villa et al, 2010;Kumar et al, 2012), but not all (Boehme et al, 2009) in the rituximab era.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This may again reflect the superior effect of rituximab in controlling systemic disease. The reported parenchymal recurrences in earlier studies were estimated at only 25% (van Besien et al, 1998;Hollender et al, 2002;Tilly et al, 2003). However, we observed a strikingly higher proportion of parenchymal-only relapses (62Á5%) compared to leptomeningeal or parenchymal/leptomeningeal relapses as seen by some groups (Villa et al, 2010;Kumar et al, 2012), but not all (Boehme et al, 2009) in the rituximab era.…”
Section: Discussionmentioning
confidence: 93%
“…The median time from diagnosis to detection of CNS disease is <1 year, suggesting that seeding of the CNS occurs early in the course of disease (van Besien et al, 1998;Haioun et al, 2000;Feugier et al, 2004;Bernstein et al, 2009;Korfel, 2011). The frequency of CNS recurrence varies with reported incidence rates of 5-7% in diffuse large B-cell lymphoma (DLBCL) (van Besien et al, 1998;Zinzani et al, 1999;Hollender et al, 2002;Feugier et al, 2004;Herrlinger et al, 2009). Half of the relapses are isolated to the CNS (leptomeningeal disease more common than parenchymal) while the rest occur in the context of progressive systemic disease (Lim et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have suggested escalation to high dose therapy as consolidation therapy in first CR for those with secondary CNS involvement at the time of diagnosis, as this group has poor outcomes with current treatment. An early study in 24 patients receiving ASCT after CNS relapse of lymphoma showed disappointing results, with only 4 long-term survivors amongst transplant recipients (van Besien et al, 1998). More recently, encouraging results have been demonstrated in patients transplanted in first CR (Cote et al, 2012) and in first or second CR (Ferreri et al, 2014;Chen et al, 2014;Oh et al, 2015;Ferreri et al, 2015b;Damaj et al, 2015;Korfel et al, 2013;Doorduyn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary central nervous system (CNS) lymphoma (SCNSL), defined as lymphoma involvement both within and outside the CNS at the time of diagnosis, or CNS relapse of a systemic lymphoma, is a rare but aggressive entity, which typically carries a poor prognosis (Villa et al, 2010;van Besien et al, 1998). Diagnoses have increased in recent years, probably due to improved diagnostics and more effective treatments for systemic lymphoma resulting in longer survival rather than a genuine increase in incidence (van Besien et al, 1998). Despite this, there remains a paucity of data on appropriate treatment strategies, with the majority of guidelines based on expert opinion or from extrapolation of studies involving patients with non-CNS lymphoma or primary CNS lymphoma (Rubenstein et al, 2013;Tomita et al, 2006;Bromberg et al, 2013).…”
mentioning
confidence: 99%